Influence of the ABC Transporter YtrBCDEF of Bacillus subtilis on Competence, Biofilm Formation and Cell Wall Thickness - Benda, Martin; Schulz, Lisa Maria; Stülke, Jörg; Rismondo, Jeanine (Frontiers in Microbiology, 2021)
Bacillus subtilis develops genetic competence for the uptake of foreign DNA when cells enter stationary phase and a high cell density is reached. These signals are integrated by the competence transcription factor ComK, which is subject to transcriptional, post-transcriptional and post-translational regulation. Many proteins are involved in the development of competence, both to control ComK activity and to mediate DNA uptake. However, for many proteins, the precise function they play in competence development is unknown. In this study, we assessed whether proteins required for genetic transformation play a role in the activation of ComK or rather act downstream of competence gene expression. While these possibilities could be distinguished for most of the tested factors, we assume that two proteins, PNPase and the transcription factor YtrA, are required both for full ComK activity and for the downstream processes of DNA uptake and integration. Further analyses of the role of the transcription factor YtrA for the competence development revealed that the overexpression of the YtrBCDEF ABC transporter in the ytrA mutant causes the loss of genetic competence. Moreover, overexpression of this ABC transporter also affects biofilm formation. Since the ytrGABCDEF operon is naturally induced by cell wall-targeting antibiotics, we tested the cell wall properties upon overexpression of the ABC transporter and observed an increased thickness of the cell wall. The composition and properties of the cell wall are important for competence development and biofilm formation, suggesting that the observed phenotypes are the result of the increased cell wall thickness as an outcome of YtrBCDEF overexpression.